Due diligence neglected: managing human resources and organisational culture in mergers and acquisitions - F. M. Horwitz; K. Anderssen; A. Bezuidenhout; S. Cohen; F. Kirsten; K. Mosoeunyane; N. Smith; K. Thole; A. Van Heerden (South African Journal of Business Management, 2002)
The aim of this article is to identify attributes of organisational culture and human resource practices required for successful transitions in mergers and acquisitions. Using primary data from five case studies on mergers and acquisitions, findings show that where neglect of two key `soft' due diligence factors of cultural and human resource compatibility occurs, transition and effective integration of the new entity is hampered. The need for a coherent integration plan including joint teams, effective communication and other appropriate human resource practices is considered vital for successful acculturation. A model for both managerial policy and further research is proposed.
Keywords: 650